Case reportMyocardial infarction complicated by acute severe mitral regurgitation and cardiogenic shock. The importance of effective intra-aortic balloon pump therapy. A case report - Krynicki, Romuald; Sobocińska, Agnieszka (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Severe functional mitral regurgitation in acute myocardial infarction may be one of the main reasons for cardiogenic shock. According to data from the SHOCK registry, this happens in 6.9% of cases of acute myocardial infarction complicated by heart failure. The only way to significantly improve the prognosis is the use of intra-aortic balloon pump (IABP) and urgent coronary revascularization. We describe a patient with acute myocardial infarction without ST-segment elevation, complicated by severe mitral regurgitation, successfully treated with IABP and percutaneous coronary intervention of the infarct-related coronary artery.